PROGRAM KAMPUS MENGAJAR MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI SERTA MENANGGULANGI BULLYING DI SMPN 13 LHOKSEUMAWE - Syarifah Maihani; Muhammad Iqbal; Cut Khairani; Desyan Ria; Kumita Kumita; Zulfikar Zulfikar (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service was stimulated by Kampus Mengajar (Campus Teaching) activities which are a form of implementation of the Merdeka Belajar - Kampus Merdeka (MBKM) program from the Ministry of Education, Culture, Research and Technology. This program was based on the ineffective implementation of learning that was carried out during the Covid-19 pandemic. This could be seen from the decrease in students' interest in learning, the level of understanding of students when learning and students' literacy and numeracy abilities. The next problem was that since school activities have gone offline, interactions were getting more intense, communicating with other people can be done directly. However, intense interactions can also be the reason why bullying occurs at school. These problems affected the effectiveness of the learning process at SMP Negeri 13 Lhokseumawe. The method used in this activity was literacy and numeracy habituation activities as well as a literature study approach regarding basic theory, impact, distribution and ways to deal with bullying. The end result of this activity was the habituation of students' literacy and numeracy at SMP Negeri 13 Lhokseumawe and stopping bullying activities in schools in increasing the role and real contribution of higher education for school students in national development.